Pelatihan Class Make Up Art bagi Masyarakat Desa Patupangan Kecamatan Barus Kabupaten Tapanuli Tengah - ‘Ainun Hasibuan, Nur; Irsyan Tanjung, Andrian; Aritha Panggabean, Sriayu; Daulay, Fitryany (COVIT (Community Service of Tambusai), 2023)
The aim of implementing the Community Partnership Service (PKM) program is to improve their skills in applying make-up, especially bridal make-up. This training also aims to improve the abilities of training participants so they can fill or open jobs so that they automatically reduce unemployment and can increase the income of the people of Patupangan Village. The training implementation includes 3 stages, namely: (1) Training Preparation Stage, (2) Training Implementation Stage, (3) Final Evaluation Stage. PKM's community service partners are the Patupangan Village Community, Barus District, Central Tapanuli Regency. The partners' most important problem is how to improve the economy of the people of Patupangan Village, Barus District, Central Tapanuli Regency so that it becomes better and develops through Make Up Art Class training. Apart from this, it is hoped that the people of Patupangan Village, Barus District, Central Tapanuli Regency will increasingly understand business opportunities by taking advantage of existing opportunities and being able to provide decent profits. It is hoped that this program will run well and increase people's insight. The expected outcome of this mentoring program is the publication of scientific works in proceedings and national journals with ISSN.